2017
DOI: 10.1002/ajmg.c.31566
|View full text |Cite
|
Sign up to set email alerts
|

A review of endophenotypes in schizophrenia and autism: The next phase for understanding genetic etiologies

Abstract: Many psychiatric disorders are caused by multiple genes and multiple environmental factors, making the identification of specific genetic risk factors for these disorders difficult. Endophenotypes are behaviors or characteristics that are intermediate between the genotype and a phenotype of interest. Because they are more directly related to the gene action than is the endpoint disorder, they may be useful in the identification of specific genes related to psychiatric disorders and the classification of disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Most notably, the astrocyte-specific deletion of Nrxn1 significantly impaired the pre-pulse inhibition of the startle response ( Fig. 7L-7N), a behavioral change that is characteristically observed in patients with schizophrenia (DiLalla et al, 2017;Javitt et al, 2015). Whereas the acoustic startle response itself was normal ( Fig.…”
Section: Deletion Of Nrxn1 From Astrocytes Impairs Spontaneous Synaptmentioning
confidence: 81%
See 1 more Smart Citation
“…Most notably, the astrocyte-specific deletion of Nrxn1 significantly impaired the pre-pulse inhibition of the startle response ( Fig. 7L-7N), a behavioral change that is characteristically observed in patients with schizophrenia (DiLalla et al, 2017;Javitt et al, 2015). Whereas the acoustic startle response itself was normal ( Fig.…”
Section: Deletion Of Nrxn1 From Astrocytes Impairs Spontaneous Synaptmentioning
confidence: 81%
“…In particular, we found that deletion of Nrxn1 in astrocytes impaired AMPAR-mediated synaptic transmission and long-term synaptic plasticity, while deletion of Nrxn1 in neurons impaired NMDAR-mediated synaptic transmission. Furthermore, deletion of Nrxn1 in astrocytes disrupted a common measure of sensorimotor gating, pre-pulse inhibition, which is of interest given that such an impairment represents a characteristic endophenotype of schizophrenia (DiLalla et al, 2017;Javitt et al, 2015) and that NRXN1 mutations represent the most common singlegene mutations in schizophrenia (Hu et al, 2019;Marshall et al, 2017;Rees et al, 2014).…”
Section: Disucssionmentioning
confidence: 99%
“…An extensive search for candidate endophenotypes has been conducted for some psychiatric disorders, including obsessive–compulsive disorder (Zhang et al, 2015 ), bipolar disorder (Bora et al, 2009 ), autism (Delorme et al, 2007 ), and attention deficit hyperactivity disorder (Albrecht et al, 2008 ). Most searches for endophenotype markers of SZ have found links to brain network connectivity (Chahine et al, 2017 ), gene expression (DiLalla et al, 2017 ), and psychophysiological organization (Liu M. et al, 2016 ). However, to date, few studies of SZ endophenotype have focused on neurocognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phenotype heterogeneity means that the same genotype may produce different phenotypes. The alternate approach to find the relationship between genotype and phenotype may be endophenotypes that will be useful in detecting genes contributing to SCZ [19,20]. However, the studies of endophenotypes (characteristics that are intermediate between the genotype and a phenotype of interest) associated with SCZ are not yet enough.…”
Section: Genetics Of Schizophrenia 21 An Overviewmentioning
confidence: 99%